Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share Terhadap Kemampuan Komunikasi Matematis Peserta Didik Kelas VII SMPN 1 Canduang - NUR RAHMAH AMIN (Jurnal Edukasi dan Penelitian Matematika, 2019)
This experimental research, which is implemented in SMPN 1 Canduang 7th grade academic of 2018/2019. Investigating the mathematical communication skills of students who learn by applying the cooperative learning model think pair share is the purpose of this research. After the research, it was found that the average score of mathematical communication skills of students who learned by applying the cooperative learning model think pair share was better than the average score of mathematical communication skills of students who studied with conventional learning.  Keywords – Cooperative learning, think pair share, mathematics communication